2019
DOI: 10.2337/dc18-2585
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Glycolytic Enzymes and Pyruvate Kinase M2 in Type 1 and 2 Diabetic Nephropathy

Abstract: Elevated glycolytic enzymes in renal glomeruli correlated with preservation of renal function in the Medalist Study, individuals with ‡50 years of type 1 diabetes. Specifically, pyruvate kinase M2 (PKM2) activation protected insulin-deficient diabetic mice from hyperglycemia-induced glomerular pathology. This study aims to extend these findings in a separate cohort of individuals with type 1 and type 2 diabetes and discover new circulatory biomarkers for renal protection through proteomics and metabolomics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 48 publications
3
61
1
Order By: Relevance
“…We found that the plasma PKM2 levels increased in patients with diabetes, which was consistent with the findings of previous studies showing elevated serum PKM2 level in some inflammatory diseases [31][32][33]. Plasma PKM2 level is associated with type 1 and type 2 diabetic nephropathy; thus, the assessment of serum PKM2 level is important [34]. Th17 differentiation is involved in the pathological progression of DN [35].…”
Section: Resultssupporting
confidence: 91%
“…We found that the plasma PKM2 levels increased in patients with diabetes, which was consistent with the findings of previous studies showing elevated serum PKM2 level in some inflammatory diseases [31][32][33]. Plasma PKM2 level is associated with type 1 and type 2 diabetic nephropathy; thus, the assessment of serum PKM2 level is important [34]. Th17 differentiation is involved in the pathological progression of DN [35].…”
Section: Resultssupporting
confidence: 91%
“…Accumulating studies demonstrated that disturbances of glucose metabolic pathways, particularly, pyruvate kinase (PK M2) depression and the Warburg phenomenon, glomerular microvascular endothelial mitochondrial dysfunction, and endoplasmic reticulum stress in renal proximal tubular epithelial cells all stimulated by hyperglycemia (HG) play crucial roles in DN onset and progression in diabetic rodent models and patients [ 3 7 ]. Specifically, renal hypoxia, oxidative stress, inflammation, and advanced glycation end products (AGEs) are simultaneously participated in the process, leading to a vicious circle in DN exacerbation [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The circulating levels of 120 proteins were increased in diabetes patients who were protected from CKD compared with those with CKD stage 3b, which shows potential protective factors against DN. The results of integrated network analysis identified enhancement/upregulation of several novel (pyruvate kinase M2, amyloid precursor protein), as well as previously known pathways (EGFR) in CKD-protected Medalists 48 . Subsequently, the presence of plasma pyruvate kinase M2 has been confirmed in a general population of patients with type 1 and type 2 diabetes.…”
Section: Human Studies Of Protective Factors For Renal Function Lossmentioning
confidence: 88%
“…The study used kidney biopsies and proteomic as well as metabolomic approaches to identify markers whose expression patterns might explain the profound protection in this cohort. To screen for markers underlying protection from DN, the authors utilized untargeted metabolomics, as well as an aptamer-based array that measures 1123 proteins in plasma 47,48 . The circulating levels of 120 proteins were increased in diabetes patients who were protected from CKD compared with those with CKD stage 3b, which shows potential protective factors against DN.…”
Section: Human Studies Of Protective Factors For Renal Function Lossmentioning
confidence: 99%